MORAL COMPETENCE OF INDONESIA PROFESSIONAL AUDITORS - Harti Budi yanti; Hasnawati Hasnawati; Dwi Fitri Puspa; Christina Dwi Astuti (Media Riset Akuntansi, Auditing & Informasi, 2019)
This study reveals the moral competence of internal auditors and public accountants in Jakarta, Indonesia. The auditor's compliance with his professional code of ethics must be based on high morality. Accountants are professions that work on the basis of public trust. Various pressures faced by auditors. All these pressures must be faced throughout the career as an auditor and require the struggle to satisfy all of these stakeholders and refrain from various temptations with various modes of bribery.The auditor must be able to control and apply his morality to face various temptations and threats in carrying out his duties. A total of 510 auditors in this matter. The results of the study show the moral of public accountants at a high moral level, while internal auditors are at a moderate level.